Understanding of Pre-Service Teachers’ Employability Skills at Tribhuvan University - Kadel, Purna Bahadur (Tribhuvan University Journal, 2021)
This study attempts to investigate the understandings of pre-service teachers towards the importance of employability skills for being employed It also explores the main causes of the absence of the employability skills of graduate pre-service teachers at Tribhuvan University. I adopted narrative inquiry research design to carry out this study. Using quota sampling technique, four female and four male pre-service teachers were selected through purposive non-random sampling procedure to collect data. In-depth-interview was administered to them as a tool to collect data in this study. The findings of this study show that the pre-service teachers lack higher order thinking skills; there is absence of employability skills in the curriculum of M.Ed. and they lack the personal and social skills and adequate communicative skills. It is concluded that the pre-service teachers are not competent and confident enough to deliver their knowledge and skills to the students due to the lack of employability skills despite the fact that they are bright students in their subject matter.